Evaluation of Waste Engine Oil-Rejuvenated Asphalt Concrete Mixtures with High RAP Content - A. A. Mamun; H. I. Al-Abdul Wahhab (Advances in Materials Science and Engineering)
The use of large proportions of reclaimed asphalt pavement is necessary to meet the increasing demand for road construction materials in a sustainable way. One of the challenges of using a greater percentage of reclaimed asphalt pavement (>30%) is the greater stiffness of mixes incorporating it. While this stiffness problem is usually resolved by using different commercial rejuvenators, there are circumstances in which commercial rejuvenators are not available. Therefore, this study evaluates the potential of using waste engine oil as a substitute for commercial rejuvenators for the higher percentage of reclaimed asphalt pavement that could meet the increasing demand in a more sustainable way. To assess the possibility of using a higher percentage of reclaimed asphalt pavement in road construction, different percentages of reclaimed asphalt pavement (30%, 40%, and 50%) are used. Following the property of the aged binder, three different percentages (7%, 13%, and 20%) of waste engine oil are considered. Each percent of waste engine oil is incorporated with one of the three mixes. The mixes (with the minimum required Marshall criteria) are evaluated for different properties, namely, their indirect tensile strength, resilient modulus, and durability. Finally, those properties are compared to those of the mixes rejuvenated by commercial rejuvenators. It is observed that, for the aforementioned properties, 7% to 13% of waste engine oil is identical to the commercial rejuvenator for the mixes with 30% to 40% of reclaimed asphalt pavement.